Все лики любви - Алюшина Татьяна Александровна (Еще раз про любовь, 2017)
Экземпляры: (20190806) / Инвентарный номер: 35149 / Цена: / Сис.шифр: 84(2Рос=Рус) / Авт.знак: А 59 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)